In ∆ABC, prove the following:
Question:

In ∆ABC, prove the following:

$2(b c \cos A+c a \cos B+a b \cos C)=a^{2}+b^{2}+c^{2}$

Solution:

$\mathrm{LHS}=2(b c \cos A+c a \cos B+a b \cos C)$

On using the cosine law, we get:

$\mathrm{LHS}=2\left[b c\left(\frac{b^{2}+c^{2}-a^{2}}{2 b c}\right)+c a\left(\frac{a^{2}+c^{2}-b^{2}}{2 a c}\right)+a b\left(\frac{a^{2}+b^{2}-c^{2}}{2 a b}\right)\right]$

$=b^{2}+c^{2}-a^{2}+a^{2}+c^{2}-b^{2}+a^{2}+b^{2}-c^{2}$

$=a^{2}+b^{2}+c^{2}=\mathrm{RHS}$

Hence proved.

Administrator

Leave a comment

Please enter comment.
Please enter your name.